Extraction and Characterization of Antimicrobial surgical Suture from the bast of Tinospora Cordifolia - Shohag Chandra Das; Mohammad Abbas Uddin (Journal of Natural Fibers, 2022)
Tinospora cordifolia, a climbing plant of south-east Asia, has been used as an Ayurveda for thousands years for its extraordinary medicinal properties. Two of its special properties are antimicrobial and anti-infection property. The objective of the study is to produce surgical suture from the bast of Tinospora cordifolia and evaluate the related chemical, physical and mechanical properties of that suture. In this work, the antimicrobial activity analysis by agar disc diffusion method, tensile strength analysis with digital single thread strength tester for both straight pull and knot pull, creep test, thread count by Beesley’s Balance, moisture analysis by Reynold & Branson rapid regain tester and surface roughness analysis by Homel roughness tester have been conducted. The Agar disc diffusion method indicates the thread contains antimicrobial properties, tensile strength is perfect for being used as a surgical suture with 38% reducing in knot pull than straight pull, fineness is also in the range where moisture content and regain is more than most of the natural fibers with higher roughness, lacking, suggesting a perfect natural surgical suture for Tex-medical applications.